Timing of influenza epidemics and vaccines in the American tropics, 2002–2008, 2011–2014. Issue 3 (8th February 2016) - Durand, Lizette Olga; Cheng, Po‐Yung; Palekar, Rakhee; Clara, Wilfrido; Jara, Jorge; Cerpa, Mauricio; El Omeiri, Nathalie; Ropero‐Alvarez, Alba Maria; Ramirez, Juliana Barbosa; Araya, Jenny Lara; Acosta, Belsy; Bruno, Alfredo; et al.
Abstract : Background: Influenza‐associated illness results in increased morbidity and mortality in the Americas. These effects can be mitigated with an appropriately chosen and timed influenza vaccination campaign. To provide guidance in choosing the most suitable vaccine formulation and timing of administration, it is necessary to understand the timing of influenza seasonal epidemics. Objectives: Our main objective was to determine whether influenza occurs in seasonal patterns in the American tropics and when these patterns occurred. Methods: Publicly available, monthly seasonal influenza data from the Pan American Health Organization and WHO, from countries in the American tropics, were obtained during 2002–2008 and 2011–2014 (excluding unseasonal pandemic activity during 2009–2010). For each country, we calculated the monthly proportion of samples that tested positive for influenza. We applied the monthly proportion data to a logistic regression model for each country. Results: We analyzed 2002–2008 and 2011–2014 influenza surveillance data from the American tropics and identified 13 (81%) of 16 countries with influenza epidemics that, on average, started during May and lasted 4 months. Conclusions: The majority of countries in the American tropics have seasonal epidemics that start in May. Officials in these countries should consider the impact of vaccinating persons during April with the Southern Hemisphere formulation.